Diagnóstico bioquímico y hematológico de los trastornos del metabolismo en población infanto-juvenil - Moyòn Llamuca, Janeth Patricia (2022)
ABSTRACT: Metabolic disorders develop into Metabolic Syndrome, one of the leading health problems worldwide. This project aimed to diagnose metabolic disorders through biochemical and hematological tests in the infant-juvenile population. A descriptive, documentary, cross-sectional, and retrospective methodology was used because the information was obtained from scientific sources such as Scielo, Pubmed, Medigraphic, Scopus, Dialnet, and repository theses. It was considered a qualitative study because there is no manipulation of variables, and it is simply a description of previously published studies. The study population consists of 115 bibliographic sources with a time range between 2011 and 2021, obtaining a sample of 35 documents updated within the inclusion criteria, giving as results in populations between 5-16 years who applied biochemical tests based on the criterion ATPIII. The infant-juvenile population must present at least three components to determine the presence of Metabolic Syndrome, with the most outstanding being the following tests with their altered values with a glucose 100 mg/dL, triglycerides 110 mg/dL, and the decrease of cHDL 40 mg/dL. The majority of people suffering from this disease have altered values. It is also because they have an inadequate diet with little nutritional input and a sedentary lifestyle. For this reason, it is essential to know that these clinical laboratory tests can be used to diagnose pathologies with greater severity.